A New MPPT Technique for Fast and Efficient Tracking under Fast Varying Solar Irradiation and Load Resistance. (4th February 2020) - Xu, Libin; Cheng, Ruofa; Yang, Jiajing
Abstract : The maximum power point tracking (MPPT) is a strategy that allows imposing the PV array operation point on the maximum power point (MPP) or close to it under any environmental condition. The conventional incremental conductance (INC) algorithm is the most popular algorithm. But due to the fixed step size, its response speed is low under the rapid change of the solar irradiation level or load resistance. In this paper, a new MPPT technique is proposed to enhance the response speed. It consists of two stages: (1) the computing stage and (2) the regulating stage. The computing stage includes the coarse positioning operation and fine positioning operation. And an initial value of the duty cycle is generated in the computing stage, according to the characteristics of the DC-DC converter and the characteristics of the I ‐ V curve. The regulating stage regulates the duty cycle of the DC-DC converter with a small step size, which can improve the tracking efficiency. And the computing stage can enhance the response speed. A simulation comparison of the proposed MPPT technique with other techniques is carried out in MATLAB/Simulink under different scenarios. The simulation results reveal that the response of the proposed algorithm is 4.6 times faster than that of the INC under these scenarios, and the proposed algorithm has higher efficiency.